x+ab=ax+3
x-ax=3-ab
x(1-a)=3-ab
x=(3-ab)/(1-a)
2007-01-28 11:43:34
·
answer #1
·
answered by bruinfan 7
·
0⤊
0⤋
x + ab = ax + 3
What you want to do is move everything that has an x in it to the left hand side, and everything else to the right hand side. I'll do this in steps so I can be clear.
First, I'll move the ab to the right hand side. This of course becomes -ab.
x = ax + 3 - ab
Next, we move ax to the left hand side. As a result, ax will become -ax.
x - ax = 3 - ab
Now, we *factor* x out of the terms on the left hand side.
x(1 - a) = 3 - ab
Since we want to isolate the x, we *divide* both sides by (1 - a). This gives us
x = (3 - ab) / (1 - a)
2007-01-28 11:45:39
·
answer #2
·
answered by Puggy 7
·
0⤊
0⤋
Solve for "x" > x + ab = ax + 3...
First: combine the x-variables > subtract "ax" from both sides...
x + ab - ax = ax - ax + 3
x + ab - ax = 3
Sec: subtract "ab" from both sides...
x + ab - ab - ax = 3 - ab
x - ax = 3 - ab
Third: factor the left side > find the common factor...
x(1 - a) = 3 - ab
Fourth: isolate "x" on one side > divide both sides by "1-a"...
[x(1 - a)]/1-a = (3 - ab)/1-a
*Cross cancel "like" terms...
x = (3 - ab)/1-a
2007-01-28 11:57:35
·
answer #3
·
answered by ♪♥Annie♥♪ 6
·
0⤊
0⤋
x + ab = ax + 3
x + ab -3 = ax (move all non-x terms to other side)
ab - 3 = ax - x (move all x terms to same side)
ab - 3 = (a-1)x (factor the x out of all terms on the x side)
(ab-3)/(a-1) = x (divide by a-1 to isolate x)
2007-01-28 11:45:20
·
answer #4
·
answered by Steve A 7
·
0⤊
0⤋
0. Recopy the equation: |---: x + ab = ax + 3. a million. positioned each and every of the x words on area and each and everything else on the different: |---: x - ax = 3 - ab. 2. team each and every of the x words into one expression: |---: x (a million-a) = 3 - ab. 3. Divide each and every area through regardless of is encumbering the x: |---: x = (3-ab) / (a million-a).
2016-10-16 05:48:08
·
answer #5
·
answered by Anonymous
·
0⤊
0⤋
X+ab=ax+3
subtract x from left to move to right, subtrat 3 from right to move to left
ab-3=ax-x.....factor out x
ab-3=X(a-1)....divide by (a-1)
get X=(ab-3)/(a-1)
2007-01-28 11:46:30
·
answer #6
·
answered by babbs 2
·
0⤊
0⤋
x+ab=ax+3
x+ab-ax=3 (subtract ax for both sides)
x-ax= 3-ab (subtract ab for both sides)
x(1-a)=3-ab (take out x)
x= (3-ab)/(1-a) (divide 1-a for both sides)
the second equation, you got it right.
or you calculate in side the parethsis fist
5(3)
15
2007-01-28 11:44:02
·
answer #7
·
answered by 7
·
0⤊
0⤋
what the first 2 said constance
2007-01-28 11:45:12
·
answer #8
·
answered by bad b 2
·
0⤊
1⤋
No.
2007-01-28 11:45:36
·
answer #9
·
answered by NONAME 2
·
0⤊
2⤋